2013
DOI: 10.1021/ac4035532
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Allosteric Nucleotide Sites of Tetramethylrhodamine-Labeled Aptamer for Noncompetitive Aptamer-Based Fluorescence Anisotropy Detection of a Small Molecule, Ochratoxin A

Abstract: Aptamer-based fluorescence anisotropy (FA) assay combines the advantages of affinity aptamers in good stability, easy generation, and facile labeling and the benefits of FA in homogeneous analysis, such as robustness, simplicity, and high reproducibility. By using a fluorophore-labeled aptamer, FA detection of a small molecule is not as easy as detection of protein because the binding of a small molecule cannot cause significant increase of molecular weight of the dye-labeled aptamer. The intramolecular intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 59 publications
(201 reference statements)
6
73
0
Order By: Relevance
“…gold nanoparticles, graphene, and silica nanoparticles) have been introduced in assay development by increasing the binding-induced molecular weight change (Cruz-Aguado and Penner, 2008;Cui et al, 2012;Huang et al, 2012;Liu et al, 2013;Ye, and Yin 2008;Yu et al, 2013;Zhu et al, 2011Zhu et al, , 2012 Recently, we have reported a simple and noncompetitive FA strategy for a small molecule, ochratoxin A, by using a TMR-labeled aptamer. (Zhao et al, 2014) It is based on the target-binding induced change of intramolecular interactions between TMR and the guanine (G) bases of the aptamer. The interaction significantly affects local rotation of TMR and FA of TMR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…gold nanoparticles, graphene, and silica nanoparticles) have been introduced in assay development by increasing the binding-induced molecular weight change (Cruz-Aguado and Penner, 2008;Cui et al, 2012;Huang et al, 2012;Liu et al, 2013;Ye, and Yin 2008;Yu et al, 2013;Zhu et al, 2011Zhu et al, , 2012 Recently, we have reported a simple and noncompetitive FA strategy for a small molecule, ochratoxin A, by using a TMR-labeled aptamer. (Zhao et al, 2014) It is based on the target-binding induced change of intramolecular interactions between TMR and the guanine (G) bases of the aptamer. The interaction significantly affects local rotation of TMR and FA of TMR.…”
Section: Introductionmentioning
confidence: 99%
“…In this FA strategy, TMR-labeling position of the aptamers plays a crucial role. The intramolecular interaction between TMR and G bases is distance dependent, and TMR labeling may influence the binding affinity of aptamer depending on the labeling sites (Zhao et al, 2014). An ideal labeling position allows TMR-labeled aptamer showing FA change upon target without loss in binding affinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ELISA (enzyme-linked immunosorbent assay) traditionally utilize the antibodies, but its storage is hard, and its preparation needs to long time and high cost 35 . As a new technique with excellent sensitivity for detection of OTA, Yao et al combined the magnetic purification with the system of rolling circular amplification (RCA) to reduce the noise and to enhance the signal.…”
Section: Detection Of Ochratoxin a By Combining Magnetic Nanoparticlementioning
confidence: 99%
“…11,12 Compared with conventional antibodies, aptamers show many advantages, such as more chemically stable, inexpensive, simple to be chemically modified, and so on. 13 This made aptamer probes more flexible in design various types of biosensors, including fluorescence, 14,15 chemiluminescence, 16,17 electrochemical, 18,19 or colorimetric sensors. 20,21 Among these, colorimetry aptasensor, especially gold nanoparticles based colorimetry aptasensor, has attracted much attention owing to their conveniences of visual observation and simple operations.…”
Section: Introductionmentioning
confidence: 99%